Structural and vibrational spectroscopic elucidation of sulpiride in solid state - Kecel Gündüz, Serda; Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Taylor & Francis Inc, 530 Walnut Street, Ste 850, Philadelphia, Pa 19106 USA, 2015)
The study on the conformational and vibrational behaviors of sulpiride molecule which is known as a neuroleptic or antipsychotic drug that is widely used clinically in the treatment of schizophrenic or depressive disorders is an important scientific and practical task. In here, a careful enough study of monomer and dimeric forms of sulpiridine {5-(aminosulfonyl)-N-[(1-ethyl-2-pyrrolidinyl) ethyl]-2-methoxy-benzamide (C15H23N3O4S)} is undertaken by density functional theory (DFTB3LYP) method with the B3LYP/6-31G(d,p) basis set. The conformations of free molecule were searched by means of torsion potential energy surfaces scan studies through dihedral angles D-1 (8 N, 18C, 20C, 23 N), D-2 (18C, 20C, 23 N, 25C) and D-3 (28C, 30C, 41S, 44 N) in electronically ground state, employing 6-31G basic set. The final geometrical parameters for the obtained stable conformers were determined by means of geometry optimization, carried out at DFT/B3LYP/6-31G(d,p) theory level. Afterwards, the possible dimer forms of the molecule were formed and their energetically preferred conformations were investigated. Moreover, the effect of basis set superposition error on the structure and energy of the three energetically favourable sulpiride dimers has been determined. The optimized structural parameters of the most stable monomer and three low energy dimer forms were used in the vibrational wavenumber calculations. Raman and IR (4000-400 cm(-1)) spectra of sulpiride have been recorded in the solid state. The assignment of the bands was performed based on the potential energy distribution data. The natural bond orbital analysis has been performed on both monomer and dimer geometries in order to elucidate delocalization of electron density within the molecule. The predicted frontier molecular orbital energies at DFT/B3LYP/6-31G(d,p) theory level show that charge transfer occurs within the molecule. The first-order hyperpolarizability (beta(0)) and related properties (mu and alpha) of the title molecule were also calculated.
Keywords: Vibrational spectra; Hyperpolarizability; DFT calculations; NBO; Sulpiride